Karakterisasi Morfologi dan Fisiologi untuk Mendapatkan Marka Morfologi dan Fisiologi Padi Sawah Tahan Kekeringan (-30 kPa) dan Produktivitas Tinggi (> 8 ton/ha) - Eko Sulistyono; . Suwarno; Iskandar Lubis (Jurnal Ilmu Pertanian Indonesia, 2012)
This study aims to obtain strains of drought-resistant rice with productivity more than 8 tons/ha, get critical point of soil moisture for drought-resistant rice and obtain morphological and physiological markers for drought-resistant rice. The First year researh consisted of the first experiment was arranged in a randomized block design consisting of two factors with three replications. The first factor is the frequency of irrigation is irrigation every 4, 8, 12, and 16 days. The second factor is 5 strains of rice paddies. The second experiment was arranged in a Split Plot design. The first factor as the main plot is composed control drought stress (irrigation every 2 days until the high pool of 2.5 cm) and drought stress (irrigated when soil water potential at between -30 kPa to -35.9 kPa). The second factor subplot was 100 rice strains to be selected for resistance to drought stress. The second year research was the main plot is composed of control (irrigation as farmers usually do) and drought stress (irrigated when soil water potential reached -30 kPa) and sub plot were 8 rice strains and 4 comparator varieties. Results of experiment is a critical point soil water potential of -35.9 kPa, Drought tolerant lines and production of ≥ 8 tons / ha by 8 lines of strain B12493C-MR-11-4-4, B11598C-TB-2-1-7-MR-4, TB155J-TB-MR-3, TB155J-TB-MR-3-2, B12476G-MR-20, B 12498C-MR-1-1-6, B12825E-TB-1-24, and B11598C-TB-4-1-1. The number of tiller and proline content were a marker of morphology and physiology of drought-resistant rice. Drought tolerant low land rice (-30 kPa) with high productivity (> 8 tons/ha) at farmer’s land condition were B11598C-TB-2-1-7-MR-4, TB155J-TB-MR-3, and TB155J-TB-MR-3-2.